حوكمة الشركات التجارية كآلية لمواجهة الفساد الإقتصادي - غفران لوكام; سلسبيل بن تريعة (My University, 2025)
Abstarct : This study aims to highlight the role of corporate governance as an effective mechanism in combating economic corruption, by analyzing both the conceptual and legal frameworks of corporate governance and reviewing the mechanisms that help reduce corruption practices within the economic environment. In the first chapter, the study addresses the fundamental concepts associated with governance and the key principles on which it is based, such as transparency, accountability, and responsibility. It also reviews national and international laws and regulations that govern the operations of companies and ensure their adherence to ethical and organizational behavior. The second chapter focuses on the practical mechanisms that contribute to the activation of governance within companies to combat corruption, such as strengthening the role of boards of directors, activating internal control systems, and developing financial disclosure mechanisms. The study also highlights the importance of involving stakeholders, including shareholders, employees, and the community, in monitoring performance and ensuring adherence to ethical standards. The study concludes that the effective implementation of governance principles enhances the integrity of the economic environment and reduces corruption practices within companies. ........................... الملخص: تهدف هذه الدراسة إلى تسليط الضوء على دور حوكمة الشركات التجارية كآلية فعالة في مواجهة الفساد الاقتصادي، من خلال تحليل الإطارين المفاهيمي والقانوني لحوكمة الشركات واستعراض الآليات التي تمكن من الحد من ممارسات الفساد داخل البيئة الاقتصادية في الفصل الأول، تناولت الدراسة المفاهيم الأساسية المرتبطة بالحوكمة وأبرز المبادئ التي تقوم عليها مثل الشفافية المساءلة والمسؤولية، إضافة إلى استعراض القوانين والتشريعات الوطنية والدولية التي تؤطر عمل الشركات وتضمن التزامها بالسلوك الأخلاقي والتنظيمي. أما الفصل الثاني فقد ركز على الآليات العملية التي تسهم في تفعيل الحوكمة داخل الشركات لمكافحة الفساد، مثل تعزيز دور مجالس الإدارة، تفعيل نظم الرقابة الداخلية، وتطوير آليات الإفصاح المالي، كما أبرزت الدراسة أهمية إشراك الأطراف المعنية المساهمين الموظفين والمجتمع في مراقبة الأداء وضمان الالتزام بالمعايير الأخلاقية. وخلصت إلى أن تطبيق مبادئ الحوكمة بشكل فعال يعزز من نزاهة البيئة الاقتصادية ويحد من ممارسات الفساد داخل الشركات.
Keywords: Keywords: Governance; Commercial Companies; Economic Corruption; Governance Mechanisms.; الكلمات المفتاحية: الحوكمة، الشركات التجارية، الفساد الإقتصادي، آليات الحوكمة.; Mots-clés : Gouvernance; Sociétés commerciales; Corruption économique; Mécanismes de gouvernance.